EXPERIMENTAL STUDIES AND MODELLING OF FRACTURE TOUGHNESS OF THE EPOXY SAMPLES WITH ECCENTRIC CRACKS - Korolenko, Vladimir A.; Li, Yulong; Dobryanskiy, Vasiliy N.; Solyaev, Yury O. (Journal of Applied Engineering Science, 2020)
The relevance of the work is due to the need for experimental studies to determine the mechanical characteristics of epoxy resin samples, which can be used to check the correctness of the choice of parameters and criteria for the onset of crack growth within the framework of elastic fracture mechanics, cohesive models, models such as VCCT, XFEM, etc. Thus, the article is aimed at determining the parameters of fracture toughness of samples of brittle epoxy resin with applied eccentric cracks. The leading method for the study of this problem is the experimental method, which makes it possible to determine the critical stress intensity factor for three-point bending of samples with an edge crack, as well as to study samples with an eccentric (relative to the center of the sample) location of cracks. The paper presents the results of experimental studies to determine the critical stress intensity factors for samples of brittle epoxy resin L285 with hardener H 285 (Hexion), obtained without the addition of a plasticizer. Based on calculations for symmetric samples, the critical values of the J-integral (Jc) were estimated, from which the values of the critical stress intensity factors were further estimated under the assumption of a plain stress state. The results of testing samples with asymmetric cracks are compared with the results of numerical modeling within the framework of elastic fracture mechanics with the energy fracture criterion. The materials of the article are of practical value, first of all, for the calibration of fracture mechanics models.
Keywords: epoxy resin; stress intensity; fracture criterion; fracture toughness; disruptive load; deformation